2022
DOI: 10.1016/j.jsps.2022.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional study to evaluate burnout among pharmacy staff in Saudi Arabia during COVID-19 pandemic

Abstract: Background Coronavirus disease 2019 (COVID-19) has placed healthcare workers, including pharmacists, at an increased risk of infection and has increased their workload, which could lead to burnout. Therefore, the present study aimed to measure the levels of burnout among hospital and community pharmacists in Saudi Arabia during the COVID-19 pandemic and to identify the risk factors associated with burnout. Methods In the present cross-sectional study, an online survey w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
2
4
0
Order By: Relevance
“…Most respondents are between 17 and 25 years old with an education diploma or bachelor's degree. The same results were also shown in previous research 15 , which explains that women were more concerned about the health of each family member, which affected the frequency of female respondents visiting the pharmacy. In addition, another previous study 16 also shows that women have an essential role as decision-makers in health services for themselves and their families.…”
Section: Resultssupporting
confidence: 88%
“…Most respondents are between 17 and 25 years old with an education diploma or bachelor's degree. The same results were also shown in previous research 15 , which explains that women were more concerned about the health of each family member, which affected the frequency of female respondents visiting the pharmacy. In addition, another previous study 16 also shows that women have an essential role as decision-makers in health services for themselves and their families.…”
Section: Resultssupporting
confidence: 88%
“…Both Alsulimani et al (2021) and Grande et al (2022) found that poor communication and inadequate organizational support were issues for nursing staff during the pandemic, lending credence to our findings. This conclusion agrees with that of Aljuffali et al (2022), who found that nurses felt burdened by their workload and anxious about the possibility of contracting an infectious disease.…”
Section: Responses To the Research Questionssupporting
confidence: 91%
“…An earlier study in Saudi Arabia revealed that HCWs experienced job and physiological problems due to Covid-19 (Abolfotouh et al, 2020). Numerous research conducted in Saudi Arabia claimed that the Covid-19 pandemic has an adverse effect on nurses in particular (e.g., Alsulimani et al, 2021;Aljuffali et al, 2022;Alanazi et al, 2021). However, numerous studies from Saudi Arabia recommended interventions including coping mechanisms, hospital communication and support, and emotional intelligence training to lessen the possible influence of those worries on the performance of HCWs during pandemics (e.g., Alwaqdani et al, 2021;Temsah et al, 2020;Alenazi et al, 2020).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Service examples included blood pressure monitoring for antihypertensives and reporting results to prescribers for review, measuring uric acid levels for gout management, providing COVID-19 vaccinations, prescribing antibiotics for urinary tract infections, providing and prescribing antiretrovirals for active COVID-19 infections, INR testing for warfarin management, participating in rapid antigen testing for local communities, providing assistance with infection control and telehealth services. Mitigating medication shortages and contributing to reporting household domestic abuse to police was also reported, which mirrored international studies [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 55%